Prevention of Deep Vein Thrombosis after Major Knee Surgery - A Randomized, Double-Blind Trial Comparing a Low Molecular Weight Heparin Fragment (Enoxaparin) to Placebo - Leclerc, Jacques R; Geerts, William H; Desjardins, Louis; Jobin, François; Laroche, François; Delorme, Fernand; Haviernick, Sylvie; Atkinson, Susan; Bourgouine, Jean (Thrombosis and Haemostasis, 1992)
Consecutive patients undergoing knee arthroplasty or tibial osteotomy at four participating hospitals received either enoxaparin, 30 mg subcutaneously every 12 h (n = 66) or an identicalappearing placebo (n = 65). All study medications started the morning after the operation and were continued up to a maximum of 14 days. Patients underwent surveillance with 125I-fibrinogen leg scanning and impedance plethysmography. Bilateral contrast venography was performed routinely at Day 14 or at time of discharge, if sooner. Deep vein thrombosis was detected by venography in 35 of 54 patients (65%) in the placebo group and in 8 of 41 patients in the enoxaparin group (19%), a risk reduction of 71%, P <0.0001. For the entire study group, deep vein thrombosis was detected by either venography of non-invasive tests in 37 of 64 patients (58%) in the placebo group and in 11 of 65 patients (17%) in the enoxaparin group, a risk reduction of 71%, P <0.0001. Proximal vein thrombosis was found in 19% of the placebo patients and in none of the enoxaparin patients, a risk reduction of 100%, P <0.001. Bleeding complications occurred in 5 of 65 patients (8%) in the placebo group and in 4 of 66 patients (6%) in the enoxaparin group, P = 0.71. There were no differences in the amount of blood loss, minimum hemoglobin levels and number of units of packed red cells given between the two treatment groups. We conclude that a fixed dose regimen of enoxaparin, started post-operatively, is an effective and safe regimen for reducing the frequency of deep vein thrombosis after major knee surgery.